Mathematicians and education reform - Fisher, Naomi D.; Keynes, Harvey; Wagreich, P. (Philip), 1941-; Conference Board of the Mathematical Sciences; Mathematicians and Education Reform Network NSF Workshop (1988 : University of Illinois at Chicago) (Providence, RI : American Mathematical Society, 1990)
41